The relationship between personal factors, facebook intensity and academic performance of youth students in Libya - Abusbiha, Mohamed Idries Ahmed; Mustaffa, Che Su (Elsevier Ltd., 2014)
Today, social network is very important to many people particularly for the youths in their everyday lives, integrating their online and offline experience and becoming one of the primary means of connecting and socially interacting worldwide, whether among individuals, students, business people and even governments.The purpose of this study is to propose a conceptual framework on the relationship between social network usage especially Facebook with academic performance.